2016
DOI: 10.32725/det.2016.002
|View full text |Cite
|
Sign up to set email alerts
|

Boundless Opportunities with Definite Limitations

Abstract: In our comparative analyses we tried to identify those factors that can affect the success of the projects implemented at the border region. We involved three cross-border programs into our analyses and studied the project of the Austria-Hungary, Slovenia-Hungary and Hungary-Croatia Cross-border Co-operation Programmes. In this article we have undertaken to compare the results of these analyses and find out the similarities in the factors determining the project success. We assumed that there are no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…A projektmenedzsment sikere akkor érhető el, ha a projektmenedzser rendelkezik vezetői kompetenciákkal is. Kaszás N. (2016b) 2016) megállapították, hogy a különböző országok magyar közösségeinek hálózata az EU területi együttműködési programjaiból finanszírozott projektekben nem szignifikánsan magas, bizonyos szempontból viszonylag alacsonynak is tekinthető. A politikákat és a fejlesztési intézkedéseket intenzívebben és stratégiailag kell építeni a közép-európai nemzeti kisebbségek meglévő hálózatain.…”
Section: A Határokon áTnyúló Projektek Vizsgálataunclassified
“…A projektmenedzsment sikere akkor érhető el, ha a projektmenedzser rendelkezik vezetői kompetenciákkal is. Kaszás N. (2016b) 2016) megállapították, hogy a különböző országok magyar közösségeinek hálózata az EU területi együttműködési programjaiból finanszírozott projektekben nem szignifikánsan magas, bizonyos szempontból viszonylag alacsonynak is tekinthető. A politikákat és a fejlesztési intézkedéseket intenzívebben és stratégiailag kell építeni a közép-európai nemzeti kisebbségek meglévő hálózatain.…”
Section: A Határokon áTnyúló Projektek Vizsgálataunclassified
“…On the other hand, given that in most cases SMEs are managed and run by their founders, their personality, knowledge, and perception greatly influence their decisions, including those made in marketing (Bretcu, 2014). Such personal decisions affect marketing effectiveness in the organization (Kaszás, Péter, Keller, & Kovács, 2016), as they can lead to a narrow and short-term interpretation (Bodlaj & Rojšek, 2014).…”
Section: Marketing In Smesmentioning
confidence: 99%
“…Cross-border cooperation is a highly prioritized issue for Hungary as a significant part of its population resides in the border region (Horváth, 2002). The analysis of cross-border projects has been undertaken by Kaszás, Péter, Keller & Kovács (2016a) and Kaszás, Birkner, Németh & Kovács (2016b). Kaszás et al (2016a), in their comparative analysis, identified the main factors contributing to the success of cross-border projects of Austria and Hungary, Slovenia and Hungary, and Hungary and Croatia.…”
Section: Examination Of Cross-border Projectsmentioning
confidence: 99%
“…The analysis of cross-border projects has been undertaken by Kaszás, Péter, Keller & Kovács (2016a) and Kaszás, Birkner, Németh & Kovács (2016b). Kaszás et al (2016a), in their comparative analysis, identified the main factors contributing to the success of cross-border projects of Austria and Hungary, Slovenia and Hungary, and Hungary and Croatia. Their findings point to the influence of organisational and individual factors such as time, project manager's authority and management competence on project implementation.…”
Section: Examination Of Cross-border Projectsmentioning
confidence: 99%